Pulmonary Artery Pseudoaneurysms: Insights and Interventions - Ung Bae Jeon (Journal of the Korean Society of Radiology)
See the article, “Angiographic Insights and Endovascular Intervention in Pulmonary Artery Pseudoaneurysms: A Comprehensive Clinical and Pictorial Essay”, in volume 85 on page 1083-1096 (https:// doi.org/10.3348/jksr.2023.0161).